OPPORTUNITIES FOR EXTRACURRICULAR EDUCATIONAL WORK HIGHER EDUCATIONAL INSTITUTION IN THE FORMATION OF COMMUNICATIVE CULTURE FUTURE TEACHERS - Havrylyuk, O.O. (Pedagogy of Higher and Secondary Education, 2007)
At this article is considered components of educational work of university and so its possibilities on a way of forming of communicative culture of students.